Victorious and vulnerable : why democracy won in the 20th century and how it is still imperiled - Gat, Azar (Hoover studies in politics, economics, and society., 2010)
In the blink of an eye, liberal democracy's moment of triumph was darkened by new threats, challenges, and doubts. Rejecting the view that liberal democracy's twentieth-century victory was inevitable, distinguished student of war Azar Gat argues that it largely rested on contingent factors and was more doubtful than has been assumed. The world's liberal democracies, with the United States at the forefront, face new and baffling security threats, with the return of capitalist nondemocratic great powers--China and Russia--and the continued threat of unconventional terror. The democratic peace, o.